Selection of option of pregame warm-up in handball taking into account features of force of the nervous system of sportsmen - Гант, Олена; Бикова, Олена (Slobozhanskyi Herald of Science and Sport, 2016)
Helen Gant, Helena Biykova Purpose: to develop recommendations about the organization of warm-up for handball players of 13–14 years old taking into account force of the nervous system (NS) of players. Material & Methods: 28 handball players of 13–14 years old of Kharkov and Ternovka took part in the research; methods were used: analysis of scientific and methodical literature, technique of "Tapping-test". Results: need of the search of new ways of the increase of efficiency of the competitive activity of young handball players is proved theoretically. Psychological characteristics of handball players of 13–14 years old with a different force of the nervous system are provided. Practical recommendations about the organization of pregame warm-up of handball players of 13–14 years old taking into account force of nervous system of sportsmen are developed. Conclusions: handball players of 13–14 years old can be divided into five groups, concerning force of their nervous system by the results of the conducted research: strong NS (28,57%), average (21,43%), weak (17,86%) and average and weak (14,29%), average and strong (17,86%). Recommendations about the organization and carrying out pregame warm-up of handball players of 13–14 years old, taking into account force of the nervous system of sportsmen were developed, considering the results of the psychological research of sportsmen.